Iron-induced kidney cell damage: insights into molecular mechanisms and potential diagnostic significance of urinary FTL - Punchai, Soraya; Chaiyagot, Nachayada; Artkaew, Nadthanicha; Jusakul, Apinya; Cha’on, Ubon; Thanan, Raynoo; Vaeteewoottacharn, Kulthida; Lert-Itthiporn, Worachart (Frontiers in Molecular Biosciences, 2024)
Iron overload can lead to organ and cell injuries. Although the mechanisms of iron-induced cell damage have been extensively studied using various cells, little is known about these processes in kidney cells. In this study, we first examined the correlation between serum iron levels and kidney function. Subsequently, we investigated the molecular impact of excess iron on kidney cell lines, HEK293T and HK-2. The results revealed that excess iron caused significant cell death accompanied by morphological changes. Transcriptomic analysis revealed an up-regulation of the ferroptosis pathway during iron treatment. This was confirmed by up-regulation of ferroptosis markers, ferritin light chain (FTL), and prostaglandin-endoperoxide synthase 2 (PTGS2), and down-regulation of acyl-CoA synthetase long-chain family member 4 (ACSL4) and glutathione peroxidase 4 (GPX4) using real-time PCR and western blotting. In addition, excess iron treatment enhanced protein and lipid oxidation. These findings suggest that excess iron disrupts cellular homeostasis and affects key proteins involved in kidney cell death. Supportively, an inverse correlation between urinary FTL protein level and kidney function was observed. In conclusion, our study demonstrated that high iron levels caused kidney cell damage. Additionally, urinary FTL might be a useful biomarker to detect kidney damage caused by iron toxicity. Our study also provided insights into the molecular mechanisms of iron-induced kidney injury, discussing several potential targets for future interventions.